A Nitrogen-Rich Covalent Triazine Framework as a Photocatalyst for Hydrogen Production - Ruizhi Gong; Liuliu Yang; Shuo Qiu; Wan-Ting Chen; Qing Wang; Jiazhuo Xie; Geoffrey I. N. Waterhouse; Jing Xu (Advances in Polymer Technology)
Covalent triazine frameworks (CTFs) have emerged as new candidate materials in various research areas such as catalysis, gas separation storage, and energy-related organic devices due to their easy functionalization, high thermal and chemical stability, and permanent porosity. Herein, we report the successful synthesis of a CTF rich in cyano groups (CTF-CN) by the solvothermal condensation of 2,3,6,7-tetrabromonapthalene (TBNDA), Na2(1,1-dicyanoethene-2,2-dithiolate), and 1,3,5-tris-(4-aminophenyl)-triazine (TAPT) at 120°C. XRD, SEM, and TEM characterization studies revealed CTF-CN to be amorphous and composed of ultrathin 2D sheets. CTF-CN possessed strong absorption at visible wavelengths, with UV-vis measurements suggesting a band gap energy in the range 2.7-2.9 eV. A 5 wt.% Pt/CTF-CN was found to be a promising photocatalyst for hydrogen production, affording a rate of 487.6 μmol g-1 h-1 in a H2O/TEOA/CH3OH solution under visible light. The photocatalytic activity of CTF-CN was benchmarked against g-C3N4 for meaningful assessment of performance. Importantly, the 5 wt.% Pt/CTF-CN photocatalyst exhibited excellent thermal and photocatalytic stability. Further, as a nitrogen-rich porous 2D material, CTF-CN represents a potential platform for the development of novel electrode material for fuel cells and metal ion batteries.